Effective removal of pollutants and colour from palm oil mill effluent final discharge using bioadsorbent from palm oil industry - Mubarak, S. F.; Z., Nahrul Hayawin; Ibrahim, M. F.; Abd Aziz, S. (Springer, 2022)
The palm oil industry produces a high amount of palm oil mill effluent (POME) every year, which can potentially cause catastrophic contamination to the environment if not treated properly. Due to strict regulation by the Department of Environment Malaysia, POME final discharge must be treated until the pollutants and colour level are below the regulated standard. Therefore, a batch adsorption study has been conducted using activated carbon (AC) produced from oil palm kernel shells (OPKS) to treat the POME final discharge. The OPKS-AC was generated by using the double-insulated carbonisation–activation reactor. The treated OPKS showed excellence characteristics as bioadsorbent with surface area of 730.91 m2 g−1 and microporous pore size distribution of 2.67 nm. The treatment of POME final discharge by using OPKS-AC had successfully reduced the level of pollutants and colour by up to 91% of biochemical oxygen demand (BOD), 87% of chemical oxygen demand (COD), 74% of total suspended solids (TSS), and 97% colour. The equilibrium points were reached after 480 min of contact time for COD, TSS and colour and 540 min for BOD using OPKS-AC dosage of 250 g L−1. The isotherm modelling showed that the adsorption behaviour onto OPKS-AC fitted the Langmuir isotherm model. Overall, the OPKS-AC can significantly remove the pollutants and colour of POME final discharge, which fit the kinetic model tested.